Role of kuhn-tucker conditions in elasticity equations in terms of stresses - Chraptovič, Ela; Atkočiūnas, Juozas (Journal of Civil Engineering and Management, 2000)
Solution of the elasticity problem in terms of stresses leads to the stress vector six components, satisfying the Beltrami compatibility eqns and boundary conditions, evaluation. A direct integration of the nine differential eqns system in respect of the six stress components is difficult to realise practically. This is the reason why often the Casigliano variation principle to solve the boundary elasticity problem in terms of stresses is applied. An application of the above-mentioned principle ensures the satisfaction of all the six Saint-Venant strain compatibility eqns (see the works of Southwell, Kliushnikov, a.o.). Castigliano variation principle does not define the number of independent strain compatibility eqns. Thus, it is not clear whether the elasticity problem eqns system in terms of stresses is over-defined or not. The strain compatibility eqns for an ideal elastic body is investigated in the article by means of the mathematical programming theory. A mathematical model to evaluate the statically admissible stresses is formulated on the basis of complementary energy minimum principle. It is proved that the strain compatibility eqns mean the Kuhn-Tucker optimality conditions of the mathematical programming problem. The method to formulate the strain compatibility eqns in respect of the statically admissible stresses defining eqns formulation technique is revealed. The proposed method is illustrated to achieve the six component stresses vector in functional space for the three-dimension problem: usually the solution of the elasticity problem in terms of the stresses is realised via the nine eqns system integration. The Kuhn-Tucker conditions allowed to confirm an original but not usually applied Washizu conclusion about Cauchy geometrical compatibility eqns.Kuno ir takerio sąlygos sudarant tamprumo teorijos lygtis įtempimaisSantrauka. Tamprumo teorijos lygčių įtempimais sprendimas siejamas su radimu še[sbreve]ių įtempimų vektoriaus komponentų, tenkinančių tris kūno pusiausvyros lygtis ir šešias Beltrami priklausomybes bei kraštines sąlygas. Tiesioginis devynių diferencialinių dalinėmis išvestinėmis lygčių sistemos integravimas šešių ieškomų įtempimų funkcijų atžvilgiu yra sunkus. Todėl da[zbreve]nai kraštinis tamprumo teorijos uždavinys įtempimais sprendžiamas variaciniu Kastiljano principu, leidžiančiu gauti tapatingą šešių Sen-Venano deformacijų darnos lygčių tenkinimą (Sausvelo, Kliušnikovo ir kitų darbai). Tačiau tiesiogiai šis principas nereglamentuoja nepriklausomų deformacijų darnos lygčių skaičiaus. Lieka neaišku, ar tamprumo teorijos lygčių įtempimais sistema nėra perteklinė. Šiame straipsnyje Sen-Venano deformacijų darnos lygtys idealiai tampriam kūnui nagrinėjamos matematinio programavimo teorijos kontekste. Tam energinio principo apie papildomos energijos minimumą pagrindu sudarytas ekstremumo analizės uždavinio statiškai galimiems įtempimams modelis. Parodyta, jog deformacijų darnos lygtys yra pagal matematinio programavimo teoriją sprendžiamo analizės uždavinio Kuno ir Takerio optimalumo sąlygos. Straipsnyje pasinaudota galimybe įvairiai formuoti deformacijų darnos lygtis priklausomai nuo statiškai galimus įtempimus apibrėžiančių sąlygų. Pagal įtempimų funkcijos su šešiais komponentais vektorių įrodyta galimybė gauti šešias trimačio tamprumo teorijos uždavinio deformacijų darnos lygtis. Straipsnyje Kuno ir Takerio sąlygomis patvirtinta originali ir kol kas ne itin paplitusi Vasidzu išvada apie būtinas ir pakankamas geometrinių Koši lygčių integruojamumo sąlygas.Article in Russian.First Published Online: 26 Jul 2012